Extended-Spectrum Beta-Lactamase (ESBL) - Producing Enterobacteriaceae Isolated in Cotonou: Characteristics and Risk Factors - AFFOLABI, DISSOU (My University, 2017)
Background: Infections with Extended-Spectrum Beta Lactamases Producing-Enterobacteriaceae (ESBL-E) constitute a global pub- lic health problem particularly in sub-Saharan Africa. Objective: To determine prevalence and resistance patterns of ESBL-E and to assess the risk factors associated with infections caused by these bacteria in Cotonou. Methods: From February to August 2015, this cross-sectional study was conducted on patients from whom Enterobacteriaceae were isolated at the Microbiology Laboratory of the University Teaching Hospital in Cotonou. For each patient, demographical and clini- cal data were recorded and samples were processed using routine procedures. Isolates obtained were identified and antimicrobial susceptibility testing performed using standard laboratory methods. Results: A total of 374 strains were collected among which, 210 (56.2%) were ESBL-E. A significant percentage of the isolated ESBL-E species were Escherichia coli (40.5%) while Klebsiella pneumoniae and Enterobacter cloacae accounted for 37.1% and 21.4% respectively. Most active antibiotics on ESBL-E were imipenem, amikacin and fosfomycin with susceptibility rates of 98.9%, 97.1% and 95.1% respectively. Antimicrobial use, current hospitalization in any unit and particularly being hospitalized in the newborn unit were more significantly associated with infections with ESBL-E than no previous history of antimicrobial use, not hospitalized in any unit and no admission in a newborn unit (Odd ratios; ORs = 2.15, 3.72 and 30.15 respectively). Conclusion: The prevalence of ESBL-E was high in Cotonou and infections with ESBL-E was associated with antimicrobial use, cur- rent hospitalization and being a patient from the newborn unit.
Keywords: ESBL; Risk Factors; Resistance; Cotonou